(untitled) (The Agriculturists, 2014)
An experiment was conducted at the Disease Diagnostic Laboratory and Net House of Plant Pathology Department, Sher-e-Bangla Agricultural University, Dhaka during July 2011 to June 2012 to investigate the efficacy of some antagonistic rhizosphere microorganisms against Fusarium oxysporum f. sp. lycopersici causing Fusarium wilt of tomato. Probable 20 antagonistic bacterial isolates and one antagonistic fungal isolate (Trichoderma harzianum) from rhizosphere soil were screened out against F. oxysporum f. sp. lycopersici. Out of 20 bacterial isolates, only four (Iso-1, Iso-2, Iso-3 and Iso-4) were found effective in dual culture method. Out of all antagonists, Trichoderma harzianum produced the highest inhibition zone (75.75 %), while the lowest inhibition zone (28.39 %) was produced by Iso- 2. In blotter method, the highest prevalence of Fusarium oxysporum was observed in control (11.25%), while the lowest was in Iso-1 (0.58%) treated seeds. DOI: http://dx.doi.org/10.3329/agric.v11i2.17494 The Agriculturists 2013; 11(2) 96-103